The financial health and the usage of financial technology among young adults - Anthony, Mervin; Sabri, Mohamad Fazli; Magli, Amira Shazana; Abdul Rahim, Husniyah; Burhan@Jaohari, Nik Ahmad Sufian; Othman, Mohd. Amim; Abdullah, Haslinda (Human Resource Management Academic Research Society, 2021)
Financial health of young adults (18-29 years old) could be best achieved with the usage of financial technology (fintech) applications. Troubled by the high cost of living, the effects of Covid-19 pandemic, the jobless rate among young adults, and the years of lockdowns and masks young adults in Malaysia’s financial health has become more perilous. This study aims to understand the financial health of young adults and the usage of financial technology. Rapid developments of fintech in Malaysia are expected to contribute to improvement of young adult’s financial health. This paper uses a dataset collected through smart partnership with Malaysian Youth Council and the Malaysian Ministry of Youth and Sports. Multi-stage random sampling was used to sample a total of 651 respondents in which the data collected was analysed descriptively and inferentially using SPSS. Descriptive analysis was conducted in order to summarize the empirical analysis results with numerical representation. This study found a single young adult requiring RM871 for their monthly expenses and married young adult requiring RM3161 per month. A total of one third of respondents had sufficient income for basic needs only. In terms of financial technology, only 2.6% of respondents do not use fintech applications. One implication for policy makers is to ensure that young adults are made aware of methods they could undertake to improve their financial health through the usage of financial technology.